The Gastroprotective Activity of Ethanol Extract of Curcuma domestica Val. on Mice Induced Ethanol - HCl - Fitri Rahmania Farikha; Moch. Saiful Bachri (Indonesian Society for Cancer Chemoprevention, 2016)
Curcuma domestica Val. (CD) is one of plant used as traditional medicine in around the world. One of the benefit of CD is to treat peptic ulcers. The aim of preset study to prove that the ethanol extract of CD has gastroprotective activity. This study used 25 male mice were divided into 5 groups. Group I as a control group were given suspension of 0.5% Na-CMC, groups II, III, and IV were each given ethanol extract of CD suspense with 0.5% Na-CMC at a dose of 50 mg/kg; 100 mg/kg; 200 mg/kg respectively, and group V was given ranitidine 10 mg/kg. All groups were treated orally for 6 days, then fasted for 24 hours, on the seventh day all mice induced 3M HCl - ethanol 60% (1:1) 0.2 ml/25 gBW. One hour later, mice were sacrificed by cervical dislocation, then dissected and taken gastric. Then performed an ulcer scoring and the curative ratio is calculated later in the histopathologic test. Data were analyzed using Kolmogorov-Smirnov test and the Levene test and ANOVA followed by LSD test level of 95%. The results showed there was no significant difference between the control with dose 50 mg/kgBW (p>0.05) and showed significant difference between control with dose 100 mg/kgBW (p<0.05),dose of 200 mg/kgBW (p<0,05), and ranitidine 10 mg/kgBW (p<0.05). Curative ratio percentage dose of 100 mg/kgBW; 200 mg/kgBW, and ranitidine are 38.89%, 61.11% and 66.67 % respectively. The conclusion of this research, the ethanol extract of Curcuma domestica Val at the dose 100 mg/kgBW and 200 mg/kgBW showed have gastroprotective activity.Keywords: Gastroprotective, Curcuma domestica Val., ethanol-HCl, Gastric ulcer